2022
DOI: 10.1123/iscj.2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Science and Application: The Use of Cocreation Educational Workshops in Professional Youth Soccer

Abstract: We examined whether practice activities adopted by professional youth soccer coaches are modulated through the implementation of and engagement with cocreative evidence-based programs. Across two experiments, we used systematic observation to identify the practice activities of seven coaches across 134 sessions. In Experiment A, drill-based and games-based activities were recorded and quantified. To encourage behaviour change across the study, the systematic observation data were compared with skill acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It is reported in the literature that the usage of played-form (versus drill-based) varies between organizations and communities of practice, 86 still preferring activities with focus on execution before problem-solving. [6][7][8]87 These are derived from coaches gaining their knowledge from experience and emulation of peers or coaches they had themselves in the past. 8,87 Despite increasing recommendations in favour of played-from activities made in the literature, the implementation of such approach on a larger scale seems to proceed slowly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported in the literature that the usage of played-form (versus drill-based) varies between organizations and communities of practice, 86 still preferring activities with focus on execution before problem-solving. [6][7][8]87 These are derived from coaches gaining their knowledge from experience and emulation of peers or coaches they had themselves in the past. 8,87 Despite increasing recommendations in favour of played-from activities made in the literature, the implementation of such approach on a larger scale seems to proceed slowly.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]87 These are derived from coaches gaining their knowledge from experience and emulation of peers or coaches they had themselves in the past. 8,87 Despite increasing recommendations in favour of played-from activities made in the literature, the implementation of such approach on a larger scale seems to proceed slowly. Whilst soccer federations and similar organization offer coaching education opportunities, it is worth noting here that coaches have also reported that their club or local governing body can also have an impact on practice design, 8 which could help the adoption of played-form practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study is required on the practice activities used by coaches in small/er nations, perhaps by adopting the systematic observation methodology to assess the microstructure of practice activities. This technique has proved very effective in understanding coach behaviours in large/r nations 55,62,63 and how coaches may adopt evidenced-based practice activities that are optimal for skill acquisition in soccer 64 . Moreover, previous studies examining the developmental activities of soccer players from different countries have shown variability in type and amount of activities across development 32,36 , coupled with the lack of examination of developmental activities in small/er less established soccer nations, so these practical implications may not be applicable to all small/er and/or less established soccer nations.…”
Section: Discussionmentioning
confidence: 99%